Chemical polymerization initiator, adhesive composition, and kit for preparing adhesive composition

The use of a chemical polymerization initiator combining thiourea, peroxyester, divalent copper, arylborate, and sulfite salts in adhesive compositions addresses the issue of insufficient adhesion to dentin, achieving enhanced adhesion and stability in wet and oxidizing conditions.

JP7658536B2Active Publication Date: 2025-04-08TOKUYAMA DENTAL CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021074181
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-07-20
Filing Date
2021-04-26
Publication Date
2025-04-08
Estimated Expiration
2041-04-26

AI Technical Summary

Technical Problem

Adhesive compositions used in dental applications, particularly when applied to dentin, often exhibit insufficient adhesion strength due to the presence of water and oxidizing components, despite using peroxyester-based chemical polymerization initiators.

Method used

A chemical polymerization initiator comprising a thiourea compound, a peroxyester, a divalent copper compound, an arylborate compound, and a sulfite salt, with the absence of hydroperoxides, is used in combination with acidic and non-acidic monomers to form an adhesive composition that maintains high curability and storage stability while achieving excellent adhesion even in wet and oxidizing environments.

Benefits of technology

The proposed adhesive composition demonstrates higher adhesion strength to dentin compared to conventional compositions, even in the presence of water and oxidizing components, while maintaining high curability and storage stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007658536000001
    Figure 0007658536000001
  • Figure 0007658536000002
    Figure 0007658536000002
  • Figure 0007658536000003
    Figure 0007658536000003
Patent Text Reader

Abstract

To provide, in an adhesive composition in which a chemical polymerization initiator is blended in a monomer component containing (g) an acidic group-containing polymerizable monomer and (h) an acidic group non-containing polymerizable monomer, a system exhibiting high-hardness and high storage stability, and containing more water and the acidic component, in particular an adhesive composition capable of exhibiting excellent adhesiveness even when applied to a dentine.SOLUTION: As a chemical polymerization initiator, a chemical polymerization initiator containing (a) a thiourea compound, (b) a peroxyester, (c) a divalent copper compound and (d) an aryl borate compound and (e) a sulfite, substantially not containing hydroperoxide, is used, the adhesive composition containing the monomer component and the initiator are packaged into two such that the (a), (d), and (e) do not coexist with the (g), and stored.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a chemical polymerization initiator, an adhesive composition, and a kit for preparing an adhesive composition. [Background technology]

[0002] In the dental field, radical polymerization curable compositions in which a polymerization initiator is mixed with a radical polymerizable monomer such as (meth)acrylate are used in various materials such as bonding materials, resin cements, resin-reinforced glass ionomers, composite resins, etc. When these materials are used in applications where they cannot be exposed to light or heat stimuli, chemical polymerization initiators are often used as the polymerization initiator.

[0003] Among dental materials, adhesive compositions such as bonding materials and resin cements often use acidic monomers mixed with non-acidic monomers to enhance adhesion, and thus a chemical polymerization initiator that exhibits high polymerization activity in the presence of an acid (acidic monomer) has been sought. Known chemical polymerization initiators that exhibit high polymerization activity in the presence of an acid are those that combine an oxidizing agent made of an organic peroxide with high thermal stability, such as hydroperoxides, ketone peroxides, peroxy esters, and diacyl peroxides, with a reducing agent made of an amine, a sulfinic acid compound, a thiourea compound, an oxime compound, a transition metal compound, and the like (these may function as reducing agents alone or in combination with a plurality of them, and are sometimes collectively called polymerization accelerators) (see Patent Documents 1 and 2).

[0004] Among these, a chemical polymerization initiator that combines a hydroperoxide and a thiourea compound has high storage stability and exhibits high activity in the presence of an acid, and is therefore particularly suitable for use as a chemical polymerization initiator for dental use. By selecting a specific compound as the thiourea compound or by combining it with a polymerization accelerator other than a thiourea compound, such as a copper compound, it is possible to impart various characteristics to the thiourea compound.

[0005] Incidentally, the chemical polymerization initiator immediately initiates a radical polymerization reaction when an oxidizing agent and a reducing agent come into contact in the presence of a radical polymerizable monomer. Therefore, when storing (preserving) an adhesive radical polymerization curable composition (adhesive composition) containing these chemical polymerization initiators and an acidic monomer and a non-acidic monomer, it is common to prepare a combination of two or more compositions (hereinafter sometimes referred to as "partial compositions") in which each component such as a divided polymerizable monomer component and each component of a divided chemical polymerization initiator are mixed so that the oxidizing agent and the reducing agent do not coexist, and store (preserve) each of these partial compositions (packaged separately). Then, immediately before use, the two or more partial compositions stored in a packaged state are mixed to prepare a curable composition containing all the chemical polymerization initiator components. As a result, the chemical polymerization initiator functions at the same time as mixing, so that the curable composition polymerizes and cures.

[0006] In the partial compositions in the above-mentioned individually packaged state, it is important that each of the partial compositions has high storage stability, and some of the above-mentioned adhesive compositions are known to have both high curability and high storage stability. For example, Patent Document 3 discloses a method for producing a chemical polymerization initiator using a highly active "chemical polymerization initiator that contains (a) a thiourea compound, (b) a peroxy ester, (c) a divalent copper compound, and (d) an aryl borate compound and does not substantially contain hydroperoxide" (hereinafter also simply referred to as a "peroxy ester-based chemical polymerization initiator"), and dividing each component constituting the peroxy ester-based chemical polymerization initiator into two compositions (hereinafter sometimes referred to as "partial initiator compositions") that are maintained in a state in which they cannot chemically contact each other, to produce the partial composition. It is described that in preparing the above, a first partial composition containing the (a) thiourea compound and the (d) aryl borate compound as main components and substantially free of organic peroxides, and a second partial composition containing the (b) peroxy ester, the (c) divalent copper compound, and an acidic group-containing polymerizable monomer as main components and substantially free of (b) hydroperoxides are packaged into a kit and mixed at the time of use, thereby making it possible to increase the storage stability of either partial composition. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2017-088637 A [Patent Document 2] International Publication WO2017 / 098724 Brochure [Patent Document 3] International Publication WO2019 / 131094 Brochure [Patent Document 4] JP 2020-111513 A Summary of the Invention [Problem to be solved by the invention]

[0008] However, the adhesive composition prepared using the kit disclosed in Patent Document 3 exhibits high adhesive performance when used in the absence of water, but when applied as a dental cement to dentin that contains a lot of water, the adhesive strength tends to be insufficient (see Patent Document 4). The adhesive composition disclosed in Patent Document 4 uses a peroxyester-based chemical polymerization initiator mixed with an inorganic peroxide as a chemical polymerization initiator to improve adhesive strength in the presence of water, but with regard to adhesion to dentin, the adhesiveness is not necessarily sufficient, and there is room for further improvement, presumably because dentin contains a large amount of oxygen, and the reducing agent is consumed due to the presence of the oxidizing components generated by the oxygen.

[0009] Therefore, the present invention aims to provide an adhesive radical polymerization curable composition comprising an acidic monomer and a non-acidic monomer and a chemical polymerization initiator, which exhibits curability and high storage stability equal to or greater than those of a composition containing the peroxy ester-based chemical polymerization initiator, and which can exhibit excellent adhesive properties even when used in a system containing a large amount of water or oxidizing components, particularly when used on dentin. [Means for solving the problem]

[0010] The above object can be achieved by the present invention. That is, the first aspect of the present invention is Represented by the general formula (1) described below The chemical polymerization initiator contains (a) a thiourea compound, (b) a peroxy ester, (c) a divalent copper compound, (d) an aryl borate compound, and (e) a sulfite, and is substantially free of hydroperoxide.

[0011] The chemical polymerization initiator of the above form (hereinafter also referred to as "the chemical polymerization initiator of the present invention") preferably further contains (f) an inorganic peroxide because a synergistic effect can be obtained. In addition, the sulfite (e) is preferably sodium sulfite.

[0012] A second embodiment of the present invention is an adhesive composition comprising a radical polymerizable monomer component consisting of (g) an acidic group-containing polymerizable monomer and (h) an acidic group-free polymerizable monomer, as well as the chemical polymerization initiator of the present invention, and substantially no hydroperoxide.

[0013] The adhesive composition of the above form (hereinafter also referred to as "the adhesive composition of the present invention") preferably further contains (i) a filler, and is preferably a dental adhesive composition.

[0014] A third embodiment of the present invention is a kit for preparing the adhesive composition of the present invention, which is composed of a combination of a first partial composition and a second partial composition packaged in a state in which they cannot physically come into contact with each other, characterized in that the first partial composition contains the (a) thiourea compound, the (d) aryl borate compound, and the (e) sulfite, and is substantially free of the (c) divalent copper compound, the (g) acidic group-containing polymerizable monomer, and a peroxide {the peroxide includes the (b) peroxy ester and the (f) inorganic peroxide.}, the second partial composition contains the (b) peroxy ester, the (c) divalent copper compound, and the (g) acidic group-containing polymerizable monomer, and is substantially free of the (a) thiourea compound, the (d) aryl borate compound, and the (e) sulfite, and at least one composition selected from the first partial composition and the second partial composition further contains the (h) acidic group-free polymerizable monomer.

[0015] In the above-mentioned adhesive composition preparation kit (hereinafter also referred to as the "kit of the present invention"), it is preferable that at least one composition selected from the first partial composition and the second partial composition further contains (i) a filler. Effect of the Invention

[0016] The chemical polymerization initiator of the present invention exhibits high activity even in the presence of an acid (acidic monomer) like the conventional peroxyester-based chemical polymerization initiator not containing (e) sulfite, and when it is mixed with an acidic monomer and a non-acidic monomer to prepare the adhesive composition of the present invention (adhesive radical polymerization curable composition), the adhesive composition of the present invention can be highly cured and can be packaged and stably stored (preserved) for a long period of time. Furthermore, by using the chemical polymerization initiator of the present invention, high adhesiveness can be obtained even when used in a system containing a large amount of water or oxidizing components (especially when used on dentin) compared to adhesive radical polymerization curable compositions containing conventional peroxyester-based chemical polymerization initiators.

[0017] Patent Document 4 describes that the same effect as that of the present invention can be obtained by adding an inorganic peroxide to a peroxyester-based chemical polymerization initiator containing the above-mentioned (a) to (d). However, it has now been revealed for the first time that the above-mentioned effect can be obtained by adding (e) a sulfite without adding an inorganic peroxide, and that a synergistic effect, i.e., higher adhesion to dentin, can be obtained when a sulfite and an inorganic peroxide are used in combination. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The chemical polymerization initiator and adhesive composition of the present invention are characterized in that (e) a sulfite is blended with the conventional peroxyester-based chemical polymerization initiator and adhesive composition (containing the initiator) described in Patent Document 3, respectively, and thereby the above-mentioned effects are obtained. The kit of the present invention is characterized in that (e) a sulfite is blended with the first partial composition in the kit described in Patent Document 3.

[0019] (e) The reason why the incorporation of a sulfite improves adhesion in an environment containing relatively large amounts of water and oxidizing components while maintaining the characteristics of conventional peroxyester-based chemical polymerization initiators is not necessarily clear, and the present invention is not bound by any logic, but the inventors presume that the reason is as follows.

[0020] That is, when used in an environment in which there is no water or oxidizing components or the amount of water or oxidizing components present is extremely small, the thiourea compound, like the conventional peroxyester-based chemical polymerization initiator, comes into contact with a divalent copper compound, coordinates with the divalent copper atom constituting the divalent copper compound, and simultaneously reduces the divalent copper atom to monovalent. Next, the copper complex obtained by this reduction reaction comes into contact with the peroxyester to form a highly active (easily generates radicals) active complex, which acts together with the aryl borate compound having a curing promotion function to proceed with the curing reaction. At this time, the monovalent copper atom is oxidized again to divalent by the redox reaction accompanied by radical generation (catalytically without being deactivated or consumed), and the circulation process in which the copper atom is reused to form the active complex is repeated, which is thought to result in high polymerization activity.

[0021] On the other hand, water and oxidizing components There are relatively many In this environment, when (e) sulfite is not included (when a conventional peroxyester-based chemical polymerization initiator is used), the hydrophilicity of each chemical polymerization initiator component is insufficient, resulting in a shortage at the adhesion site and susceptibility to inhibition by oxidizing components, making it difficult for the above mechanism to function (the above catalytic cycle is difficult to operate), and polymerization activity is reduced. In contrast, by adding a sulfite, which is very hydrophilic and not easily inhibited by oxidizing components, the above catalytic cycle is able to operate smoothly, and it is believed that adhesion is improved.

[0022] The chemical polymerization initiator of the present invention, the adhesive composition of the present invention, and the kit of the present invention are not particularly different from those described in Patent Document 3, except that (e) a sulfite is blended (in the first partial composition). The present invention will be described below, including these points.

[0023] In this specification, unless otherwise specified, the expression "x~y" using the numerical values ​​x and y means "greater than or equal to x and less than or equal to y". In such an expression, when a unit is added only to the numerical value y, the unit is also applied to the numerical value x. In addition, in this specification, the term "(meth)acrylic" means both "acrylic" and "methacrylic". Similarly, the term "(meth)acrylate" means both "acrylate" and "methacrylate", and the term "(meth)acryloyl" means both "acryloyl" and "methacryloyl".

[0024] 1. Chemical Polymerization Initiator of the Present Invention The chemical polymerization initiator of the present invention is Represented by the general formula (1) described below The composition is characterized by containing (a) a thiourea compound, (b) a peroxy ester, (c) a divalent copper compound, (d) an aryl borate compound, and (e) a sulfite, and is substantially free of hydroperoxide.

[0025] Here, "substantially free of hydroperoxide" means (1) no hydroperoxide (hydroperoxide content is 0 mass%), or (2) (b) the molar ratio of peroxyester (PE) to hydroperoxide (HP): HP / PE is in the range of more than 0 and not more than 2 / 100, preferably more than 0 and not more than 1 / 300. If the chemical polymerization initiator of the present invention does not satisfy the condition of "substantially free of hydroperoxide", it becomes difficult to increase the storage stability when the adhesive composition containing the radical polymerizable monomer components consisting of (g) an acidic group-containing polymerizable monomer and (h) an acidic group-free polymerizable monomer, and the chemical polymerization initiator is divided into a plurality of partial compositions and packaged into a kit.

[0026] The (a) thiourea compound, (b) peroxyester, (c) divalent copper compound, (d) arylborate compound, and (e) sulfite used in the chemical polymerization initiator of the present invention will be described in detail below.

[0027] <(a) Thiourea compounds> A thiourea compound refers to a compound having the structure =NC(=S)-N=. In the chemical polymerization initiator of the present invention, As a thiourea compound under The thiourea compound represented by the following general formula (1) is used. 。

[0028] [ka]

[0029] In the general formula (1), R 1 , R 2 and R 3 are hydrogen atoms, Place R is a substituted or unsubstituted alkyl group, a substituted or unsubstituted cycloalkyl group, a substituted or unsubstituted aryl group, a substituted or unsubstituted heterocyclic group, a substituted or unsubstituted acyl group, a substituted or unsubstituted aralkyl group, or a substituted or unsubstituted alkenyl group; 2 is R 1 and R 3 may be bonded to any group selected from the group consisting of the above to form a ring.

[0030] Among the thiourea compounds represented by the general formula (1), from the viewpoint of storage stability, R 1 , R 2 and R 3 It is preferable that at least two of the groups R are hydrogen atoms and the remaining group is the above group other than a hydrogen atom. 2 and R 3 and are hydrogen atoms, and R 1 Thiourea compounds in which is an acyl group are particularly preferred.

[0031] Suitable usable thiourea compounds include thiourea, methylthiourea, ethylthiourea, n-propylthiourea, isopropylthiourea, cyclohexylthiourea, benzylthiourea, phenylthiourea, acetylthiourea, benzoylthiourea, adamantylthiourea, 1-(2-pyridyl)-2-thiourea, 1-(2-tetrahydrofurfuryl)-2-thiourea, N,N'-dimethylthiourea, N,N'-diethylthiourea, N,N'-di-n-propylthiourea, N, Examples of the thiourea compound include N'-diisopropylthiourea, N,N'-dicyclohexylthiourea, N,N'-diphenylthiourea, trimethylthiourea, triethylthiourea, tri-n-propylthiourea, triisopropylthiourea, tricyclohexylthiourea, tetramethylthiourea, tetraethylthiourea, tetra-n-propylthiourea, tetraisopropylthiourea, tetracyclohexylthiourea, ethylenethiourea, 4,4'-dimethylethylenethiourea, etc. Specific examples of the most suitable thiourea compound include acetylthiourea and benzoylthiourea.

[0032] In addition, the thiourea compound may be used alone or in combination of two or more. When two or more thiourea compounds are used, the mass based on the mass is the total mass of the thiourea compounds.

[0033] In the chemical polymerization initiator of the present invention, the blending amount of the (a) thiourea compound is not particularly limited, but is preferably 4 to 4800 parts by mass per 100 parts by mass of the (b) peroxyester. By satisfying this range, high polymerization activity and high storage stability can be exhibited. In order to exhibit higher polymerization activity and higher storage stability, it is more preferable to make it 13 to 875 parts by mass, and even more preferable to make it 27 to 600 parts by mass, per 100 parts by mass of the peroxyester.

[0034] <(b) Peroxyester> (b) Peroxy ester is a compound having a structure represented by RC(=O)-OO-R' (wherein R and R' are any organic group) or ROC(=O)-OO-R' (wherein R and R' are any organic group). In the chemical polymerization initiator of the present invention, peroxy esters having such a structure can be used without any particular limitation. Specific examples of peroxy esters that can be suitably used include cumyl peroxy neodecanoate, 1,1,3,3-tetramethylbutyl peroxy decanoate, t-hexyl peroxy neodecanoate, t-butyl peroxy neodecanoate, t-hexyl peroxy pivalate, t-butyl peroxy pivalate, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, 2,5-dimethyl 2,5-di(2-ethylhexanoylperoxy)hexane, t-hexyl peroxy-2-ethylhexano ...1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, 1,1, Examples of peroxyalkyl groups include t-butylperoxy-2-ethylhexanoate, t-hexylperoxyisopropyl monocarbonate, t-butylperoxy-3,5,5-trimethylhexanoate, t-butylperoxylaurate, t-butylperoxyisopropyl monocarbonate, t-butylperoxy-2-ethylhexyl monocarbonate, t-hexylperoxybenzoate, 2,5-di(benzoylperoxy)hexane, t-butylperoxyacetate, t-butylperoxy-3-methylbenzoate, and t-butylperoxybenzoate. Among these, from the viewpoints of polymerization activity and storage stability, peroxyesters having a 10-hour half-life temperature of 80°C or higher are preferably used, and t-butylperoxy-3,5,5-trimethylhexanoate, t-butylperoxylaurate, t-butylperoxy-2-ethylhexylmonocarbonate, t-butylperoxyacetate, t-butylperoxybenzoate, etc. are particularly preferably used.

[0035] The (b) peroxyester may be used alone or in combination of two or more. When two or more (b) peroxyesters are used, the standard mass is the total mass of the (b) peroxyesters.

[0036] <(c) Divalent copper compounds> In the chemical polymerization initiator of the present invention, a divalent copper compound is used as the copper compound. In addition, in the chemical polymerization initiator of the present invention, a monovalent copper compound can also be used together with the divalent copper compound, but from the viewpoint of storage stability, it is preferable that the monovalent copper compound is contained in the chemical polymerization initiator of the present invention only in a small amount to the extent that the storage stability is not affected, or is not substantially contained. In this case, it is particularly preferable that the monovalent copper compound is not substantially contained in the second partial initiator composition. When the monovalent copper compound is contained in the second partial initiator composition, the monovalent copper compound acts as a reducing agent for the peroxyester, and the storage stability may be deteriorated.

[0037] (c) The divalent copper compound may be a hydrate or anhydrous. Examples of divalent copper compounds that can be suitably used include copper chloride (II), copper sulfate (II) pentahydrate, copper nitrate (II), trifluoromethane copper sulfate (II), copper acetate (II) monohydrate, acetylacetonate copper (II), naphthenate copper (II), salicylate copper (II), benzoate copper (II), methacrylate copper (II), butyl phthalate copper (II), gluconate copper (II), dichloro(1,10-phenanthroline) copper (II), ethylenediaminetetraacetate copper (II) disodium tetrahydrate, dimethyldithiocarbamate copper (II), diethylthiocarbamate copper (II), hexafluoroacetylacetonate copper (II), bis(1,3-propanediamine) copper (II) dichloride, bis(8-quinolinolato) copper (II), and the like. These divalent copper compounds may be used alone or in combination of two or more.

[0038] Among these divalent copper compounds, from the viewpoint of high storage stability and high activity with (b) thiourea compounds, it is preferable that the ligand coordinated to the divalent copper atom constituting the divalent copper compound is (i) a halogen atom, (ii) an atomic group containing an oxygen atom, or (iii) an atomic group containing a nitrogen atom.In particular, it is more preferable that the ligand is (ii) an atomic group containing an oxygen atom, and examples of divalent copper compounds having such a ligand include copper(II) sulfate, copper(II) acetate monohydrate, and copper(II) acetylacetonate.Note that, when the (ii) ligand is an atomic group containing an oxygen atom, the atomic group containing an oxygen atom coordinates to the divalent copper atom via the oxygen atom, and when the (iii) ligand is an atomic group containing a nitrogen atom, the atomic group containing a nitrogen atom coordinates to the divalent copper atom via the nitrogen atom.

[0039] In the chemical polymerization initiator of the present invention, the amount of the divalent copper compound (c) (total amount when two or more compounds are included) is not particularly limited, but is preferably 0.002 to 250 parts by mass per 100 parts by mass of the peroxyester (b). By satisfying this range, high polymerization activity and high storage stability can be exhibited. In order to exhibit higher polymerization activity and higher storage stability, it is more preferable to set it to 0.008 to 20 parts by mass, and even more preferable to set it to 0.03 to 8 parts by mass, per 100 parts by mass of the peroxyester.

[0040] <(d) Aryl borate compounds> The aryl borate compound is not particularly limited as long as it is a compound having at least one boron-aryl bond in the molecule, but it is preferable to use a compound represented by the following general formula (2).

[0041] [ka]

[0042] In general formula (2), R 10 , R 20 and R 30are each a substituted or unsubstituted alkyl group, a substituted or unsubstituted aryl group, a substituted or unsubstituted aralkyl group, or a substituted or unsubstituted alkenyl group; R 40 , and R 50 are each independently a hydrogen atom, a halogen atom, a substituted or unsubstituted alkyl group, or a substituted or unsubstituted phenyl group; L + is a metal cation, a quaternary ammonium ion, a quaternary pyridinium ion, a quaternary quinolinium ion, or a phosphonium ion.

[0043] In addition, L in the general formula (2) + Examples of the cation include metal cations, quaternary ammonium ions, quaternary pyridinium ions, quaternary quinolinium ions, and phosphonium ions. Here, (i) the metal cation is preferably an alkali metal cation such as sodium ion, lithium ion, or potassium ion, or (ib) an alkaline earth metal cation such as magnesium ion; (ii) the quaternary ammonium ion is preferably a tetrabutylammonium ion, a tetramethylammonium ion, or a tetraethylammonium ion; (iii) the quaternary pyridinium ion is preferably a methylpyridinium ion, an ethylpyridinium ion, or the like; (iv) the quaternary quinolinium ion is preferably a methylquinolinium ion, an ethylquinolinium ion, or a butylquinolinium ion; and (v) the phosphonium ion is preferably a quaternary phosphonium ion such as a tetrabutylphosphonium ion, a methyltriphenylphosphonium ion, or the like.

[0044] Suitable examples of the arylborate compound represented by the general formula (2) include sodium salt, lithium salt, potassium salt, triethanolammonium salt, tetrabutylammonium salt, and the like of tetraphenylborate. Among these, sodium salt of tetraphenylborate is particularly preferred because it has high water solubility and therefore high curing activity in areas with a large amount of water.

[0045] In the chemical polymerization initiator of the present invention, the blending amount of the (e) aryl borate compound is not particularly limited, but is preferably 10 to 2000 parts by mass, particularly 30 to 1000 parts by mass, per 100 parts by mass of the (b) peroxy ester. By blending the amount in such a range, high curability and / or adhesiveness can be obtained when the chemical polymerization initiator of the present invention is used in an adhesive composition or an adhesive composition kit.

[0046] <(e) Sulfite> (e) As the sulfite, known sulfites such as sodium sulfite, calcium sulfite, etc. can be used without any particular limitation. From the viewpoints of polymerization activity and ease of handling, it is preferable to use sodium sulfite. In the chemical polymerization initiator of the present invention, the blending amount of the (e) sulfite is preferably 7 to 21,000 parts by mass, particularly 17 to 3,300 parts by mass, and most preferably 55 to 1,320 parts by mass, per 100 parts by mass of the (b) peroxy ester, because this allows the sulfite to exhibit high polymerization activity and high adhesive strength.

[0047] The chemical polymerization initiator of the present invention may contain (f) an inorganic peroxide and other polymerization accelerators in addition to the above-mentioned components (a) to (e). These will be described below.

[0048] <(f) Inorganic peroxide> As described in Patent Document 4, the inorganic peroxide (f) is known to have the same effect as the sulfite (e). With the chemical polymerization initiator of the present invention, the above effect can be obtained without using the inorganic peroxide (f). Therefore, from the viewpoint of minimizing the number of components and reducing costs (cost-effectiveness), the chemical polymerization initiator of the present invention may be substantially free of the inorganic peroxide (f). However, since a synergistic effect can be expected by using the inorganic peroxide in combination with the inorganic peroxide (f), it is preferable to actively incorporate the inorganic peroxide.

[0049] (f) As the inorganic peroxide, known inorganic peroxides can be used without any particular limitation, such as lithium peroxide, potassium peroxide, magnesium peroxide, calcium peroxide, barium peroxide, zinc peroxide, peroxodisulfates, peroxodiphosphates, etc. From the viewpoint of polymerization activity, it is preferable to use peroxodisulfates such as sodium peroxodisulfate, potassium peroxodisulfate, and ammonium peroxodisulfate, and it is particularly preferable to use potassium peroxodisulfate and sodium peroxodisulfate. When the inorganic peroxide (f) is actively blended with the chemical polymerization initiator of the present invention, the blending amount is preferably 7 to 21,000 parts by mass, particularly 17 to 3,300 parts by mass, and most preferably 55 to 1,320 parts by mass, per 100 parts by mass of the peroxy ester (b), because this allows high polymerization activity and high adhesive strength to be exhibited.

[0050] <Other polymerization accelerators> The chemical polymerization initiator of the present invention may be mixed with an aromatic sulfinic acid compound and a barbituric acid compound as other polymerization accelerators.

[0051] Examples of aromatic sulfinic acid compounds that can be suitably used include sodium p-toluenesulfinate, sodium benzenesulfinate, 2,4,6-trimethylbenzenesulfinic acid, 2,6-dimethylbenzenesulfinic acid, 2,6-diisopropylbenzenesulfinic acid, 2,4,6-trimethylbenzenesulfinic acid, and the sodium salt, triethanolammonium salt, and tetraethylammonium salt of 2,4,6-triisopropylbenzenesulfinic acid. Among these aromatic sulfinic acid salts, benzenesulfinic acid salts and paratoluenesulfinic acid salts are preferred because of their high reactivity and high solubility in polymerizable monomers.

[0052] Examples of barbituric acid compounds that can be suitably used include 5-butylbarbituric acid, 1,3,5-trimethylbarbituric acid, 1-cyclohexyl-5-ethylbarbituric acid, and the sodium and calcium salts of these barbituric acids.

[0053] When these are blended, the total amount of these is preferably 10 to 2000 parts by mass, and particularly preferably 30 to 1000 parts by mass, per 100 parts by mass of the (b) peroxy ester.

[0054] 2. Adhesive composition of the present invention The adhesive composition of the present invention is characterized in that it contains a radical polymerizable monomer component consisting of (g) an acidic group-containing polymerizable monomer and (h) an acidic group-free polymerizable monomer, and the chemical polymerization initiator of the present invention, and is substantially free of hydroperoxide. Here, "substantially free of hydroperoxide" means (1) that it does not contain hydroperoxide (the content of hydroperoxide is 0 mass%), or (2) that the molar ratio of (b) peroxyester (PE) to hydroperoxide (HP): HP / PE contained in the adhesive composition of the present invention is in the range of more than 0 and not more than about 2 / 100, preferably more than 0 and not more than about 1 / 300.

[0055] The mixing ratio of the (g) acidic monomer and the (h) non-acidic monomer in the radical polymerizable monomer component of the adhesive composition of the present invention is preferably such that the (g) acidic group-containing polymerizable monomer and the (h) acidic group-free polymerizable monomer are 0.1 to 50 parts by mass and the remainder is the (h) acidic group-free polymerizable monomer relative to 100 parts by mass of the radical polymerizable monomer component, and more preferably such that the (g) acidic group-containing polymerizable monomer is 1 to 30 parts by mass and the remainder is the (h) acidic group-free polymerizable monomer. The content of the chemical polymerization initiator of the present invention is preferably such that the (b) peroxyester is 0.005 to 5 parts by mass, particularly the (b) peroxyester is 0.05 to 2.5 parts by mass, relative to 100 parts by mass of the radical polymerizable monomer component.

[0056] The adhesive composition of the present invention may further contain (i) a filler, a solvent, a polymerization inhibitor, a pigment, an ultraviolet absorber, etc., as necessary. The adhesive composition of the present invention can be suitably used as a dental material, and among dental materials, it can be particularly suitably used as a dental cement or a dental adhesive. When used as a dental cement, it is preferable that the adhesive composition contains (i) a filler, and when used as a dental adhesive, it is preferable that the adhesive composition contains a solvent.

[0057] The radical polymerizable monomers used in the adhesive composition of the present invention, specifically, (g) the acidic group-containing polymerizable monomer (acidic monomer) and (h) the acidic group-free polymerizable monomer (non-acidic monomer), and (i) the filler will be described below.

[0058] <(g) Acidic Group-Containing Polymerizable Monomer (Acidic Monomer)> As the acidic monomer, a known polymerizable monomer having at least one acidic group and at least one radically polymerizable unsaturated group can be used. Here, the acidic group is one that causes an aqueous solution or water suspension of the radically polymerizable monomer having this group to exhibit acidity, and representative examples include those having a hydroxyl group such as a carboxyl group (-COOH), a sulfo group (-SO3H), a phosphinico group {=P(=O)OH}, and a phosphono group {-P(=O)(OH)2}. In addition to such hydroxyl group-containing acidic groups, examples include an acid anhydride group having a structure in which two hydroxyl group-containing acidic groups are dehydrated and condensed, and an acid halide group in which the hydroxyl group of the hydroxyl group-containing acidic group is substituted with a halogen. The radically polymerizable unsaturated group is not particularly limited and may be a known one. Examples include (meth)acryloyl-based groups such as a (meth)acryloyl group, a (meth)acryloyloxy group, a (meth)acryloylamino group, and a (meth)acryloylthio group, a vinyl group, an allyl group, and a styryl group.

[0059] As the acidic monomer, from the viewpoint of polymerization, a (meth)acrylic acid ester-based acidic group-containing polymerizable monomer is preferably used. From the viewpoint of safety to living bodies, this (meth)acrylic acid ester-based acidic group-containing polymerizable monomer is particularly suitable for use in dental materials. Only one type of acidic monomer may be used, or two or more types may be used in combination.

[0060] Examples of acidic monomers that can be suitably used include 2-(meth)acryloyloxyethyl dihydrogen phosphate, bis[2-(meth)acryloyloxyethyl]hydrogen phosphate, 2-(meth)acryloyloxyethyl phenyl hydrogen phosphate, 6-(meth)acryloyloxyhexyl dihydrogen phosphate, 6-(meth)acryloyloxyhexyl phenyl hydrogen phosphate, 10-(meth)acryloyloxydecyl dihydrogen phosphate, 1,3-di(meth)acryloylpropane-2-dihydrogen phosphate, 1,3-di(meth)acryloylpropane-2-phenyl hydrogen phosphate, and bis[5-{2-(meth)acryloyloxyethoxycarbonyl}heptyl]hydrogen phosphate.

[0061] <(h) Polymerizable monomers not containing an acidic group (non-acidic monomers)> The non-acidic monomer is not particularly limited as long as it has at least one radically polymerizable unsaturated group in the molecule and does not have an acidic group. From the viewpoint of polymerizability and safety to living bodies, a (meth)acrylic acid ester-based acidic group-free polymerizable monomer is preferably used. The non-acidic monomer may be used alone or in combination of two or more. Examples of non-acidic monomers that can be preferably used include methyl (meth)acrylate, ethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, 2,2-bis[4-(3-methacryloyloxy)-2-hydroxypropoxyphenyl]propane, 2,2-bis(methacryloyloxypolyethoxyphenyl)propane, 2-hydroxyethyl methacrylate, 2,2,4-trimethylhexamethylenebis(2-carbamoyloxyethyl)dimethacrylate, 1,10-decanediol di(meth)acrylate, etc.

[0062] In some cases, such as when the adhesive composition of the present invention is used as a dental material, the cured product of the adhesive composition may be required to have superior mechanical strength. In such cases, it is preferable to use, as the non-acidic monomer, a di-, tri- or tetra-functional radically polymerizable monomer having multiple radically polymerizable groups.

[0063] Next, compounding agents that can be suitably compounded in the adhesive composition of the present invention will be described. <(i) Filler> As the filler that can be used in the adhesive composition of the present invention, inorganic fillers, organic fillers, organic-inorganic composite fillers, etc. that are used in conventional dental materials, etc. can be used without any particular limitation. From the viewpoint of the mechanical strength of the cured product, it is preferable to use inorganic fillers and organic-inorganic composite fillers.

[0064] Examples of suitable inorganic fillers include various silicas; composite oxides containing silicon as a constituent element, such as silica-titania and silica-zirconia; clay minerals or silicates containing silicon as a constituent element, such as talc, montmorillonite, zeolite, and calcium silicate (hereinafter, these are referred to as silica-based fillers); ytterbium fluoride, yttrium fluoride, silicate glass, fluoroaluminosilicate glass, lanthanum glass, barium glass, and strontium glass. These inorganic fillers may be surface-treated with a surface treatment agent such as a silane coupling agent in order to improve compatibility with polymerizable monomers and improve the mechanical strength and water resistance of the resulting cured body. The silica-based fillers have excellent chemical stability and are easy to surface-treat with a silane coupling agent. In addition, examples of organic fillers that can be suitably used include polymethyl methacrylate, polyethyl methacrylate, methyl methacrylate-ethyl methacrylate copolymer, cross-linked polymethyl methacrylate, cross-linked polyethyl methacrylate, ethylene-vinyl acetate copolymer, styrene-butadiene copolymer, acrylonitrile-styrene copolymer, acrylonitrile-styrene-butadiene copolymer, etc. Furthermore, examples of organic-inorganic composite fillers that can be suitably used include organic-inorganic composite fillers obtained by compounding a polymerizable monomer that can be used as (e) an acidic monomer or (f) a non-acidic monomer with an inorganic filler. The compounding method is not particularly limited, and the filler may be solid or may have fine holes. From the viewpoint of the mechanical strength of the cured body, it is preferable to use an organic-inorganic composite filler in which the surface of inorganic aggregate particles is coated with an organic polymer and has fine holes, as described in the pamphlet of International Publication No. 2013 / 039169. Only one of these fillers may be used, or two or more of them may be used in combination. The shape of the filler is not particularly limited, and may be an irregular particle shape obtained by normal pulverization, or may be a spherical particle. The average particle size of the filler is not particularly limited, but is preferably about 0.01 to 100 μm, and more preferably about 0.1 to 50 μm.

[0065] The total amount of the filler (i) may be appropriately determined depending on the intended use. In particular, when used in dental materials, particularly dental cement, it is preferable to mix 65 to 1000 parts by mass with respect to 100 parts by mass of the polymerizable monomer component contained in the dental cement. From the viewpoint of kneadability and mechanical strength of the hardened body, it is more preferable to mix 150 to 400 parts by mass with respect to 100 parts by mass of the polymerizable monomer component contained in the dental cement. In addition, when the adhesive composition of the present invention is used as a dental cement, the composition of the radical polymerizable monomer component is usually 0.1 to 50 mass% based on the total mass of the radical polymerizable monomer component as (g) acidic monomer and the remainder is (h) non-acidic monomer, and preferably 1 to 30 mass% is (g) acidic monomer and the remainder is (h) non-acidic monomer. In a dental cement employing such a composition of polymerizable monomer components, the adhesiveness to tooth structure is stronger, and the adhesive durability to tooth structure and prosthetics made of various materials can be further improved.

[0066] 3. Kits of the Present Invention The kit of the present invention having the above characteristics is composed of a combination of a first partial composition and a second partial composition packaged in a state in which they cannot physically come into contact with each other, and the adhesive composition of the present invention is prepared by mixing the two partial compositions at the time of use. The first partial composition contains the (a) thiourea compound, the (d) aryl borate compound, and the (e) sulfite, and is substantially free of the (c) divalent copper compound, the (g) acidic group-containing polymerizable monomer, and peroxide {the peroxide includes the (b) peroxy ester and the (f) inorganic peroxide.}, the second partial composition contains the (b) peroxy ester, the (c) divalent copper compound, and the (g) acidic group-containing polymerizable monomer, and is substantially free of the (a) thiourea compound, the (d) aryl borate compound, and the (e) sulfite, and at least one composition selected from the first partial composition and the second partial composition further contains the (h) acidic group-free polymerizable monomer.

[0067] The kit of the present invention having the above-mentioned characteristics has high storage stability of the individually packaged first partial composition and second partial composition, and can be stably stored (preserved) in the individually packaged state for a long period of time. Therefore, it is not only useful as a storage form, but can also be distributed on the market as a product in itself.

[0068] In addition, "packaged in a state where one composition cannot come into contact with another composition" means a state in which one composition and another composition are separated and packaged by an inhibitor (packaging material) that inhibits molecular diffusion between the two. As the inhibitor (packaging material), generally, solid materials such as resin, glass, metal, and ceramics that are preferably used as materials for containers and bags are used. A typical example of a "state where one composition cannot come into contact with the other composition" is, for example, a state in which one type of composition is stored in a sealed state in a container that blocks outside air and outside light. Specific packaging forms include a form filled in a container such as a bottle, a tube, or a syringe. For example, the adhesive composition of the present invention can be prepared by i) a method in which an appropriate amount of the first agent and the second agent are applied to a mixing paper and the two are mixed with a spatula, ii) a method in which the first agent and the second agent are simultaneously extruded from a syringe with a mixing tip connected to the tip when the first agent and the second agent are in a paste form, and iii) a method in which the first agent and the second agent are collected in the same mixing dish when the first agent and the second agent are in a liquid form.

[0069] In the first and second partial compositions, "substantially free" means (1) the case where the target compound or component is not contained (content is 0% by mass), or (2) the case where the target compound or component is contained in a small amount to the extent that no significant difference in storage stability is observed compared to the case where the target compound or component is not contained. Here, in the case of (2) above, the content in each partial composition is usually 1% by mass or less, preferably 0.02% by mass or less, and particularly preferably 0.01% by mass or less.

[0070] When the adhesive composition of the present invention, which is the preparation target, contains (f) an inorganic peroxide, the (f) inorganic peroxide is contained in the second partial composition and is not substantially contained in the first partial composition. When the adhesive composition of the present invention contains an aromatic sulfinic acid compound and / or a barbituric acid compound, these compounds are preferably blended in the first agent. Furthermore, when the adhesive composition of the present invention contains (i) a filler, these components may be blended in either the first agent or the second agent, but are preferably blended in both agents because they are easily compatible and easily homogenized when mixed.

[0071] For example, when the kit of the present invention is used as a dental cement kit, it is preferable to adopt an embodiment in which the first partial composition is composed only of (a) a thiourea compound, (d) an aryl borate compound, (e) a sulfite, (h) an acidic group-free polymerizable monomer, and (i) a filler, and the second partial composition is composed only of (b) a peroxy ester, (c) a divalent copper compound, (g) an acidic group-containing polymerizable monomer, (h) an acidic group-free polymerizable monomer, and (i) a filler, or to adopt an embodiment in which (f) an inorganic peroxide is further added to the second partial composition in the above embodiment. In these embodiments, it is preferable to use acetylthiourea or benzoylthiourea as the (a) thiourea compound, sodium salt of tetraphenyl boron as the (d) aryl borate compound, sodium sulfite as the (e) sulfite, and peroxodisulfate as the (f) inorganic peroxide, respectively.

[0072] The compositions of the first partial composition (first agent) and the second partial composition (second agent) are basically determined so that when they are mixed in equal amounts {the mixing ratio of the first agent and the second agent (amount of the first agent / amount of the second agent): 1 / 1, or the mixing ratio of the first agent and the second agent (100×amount of the first agent / amount of the second agent): 100%), the composition of the adhesive composition of the present invention is obtained. Then, according to the composition thus determined, the first agent and the second agent can be easily prepared by weighing and mixing each component. Note that the above "equal amount" usually means equal amount on a mass basis, but when the composition is in a liquid state, it may be equal amount on a volume basis.

[0073] However, in actual use, that is, when the first partial composition (first agent) and the second partial composition (second agent) are mixed to prepare the adhesive composition of the present invention, the mixing ratio may not be strictly 1 / 1. In this case, it is preferable to obtain the adhesive composition of the present invention having the desired composition when mixed at a mixing ratio other than 1 / 1 (hereinafter also referred to as "designated mixing ratio"). The designated mixing ratio (this value expressed as a percentage is also referred to as "designated mixing ratio") may be appropriately determined within a range in which polymerization activity and operability are not significantly impaired. However, from the practical viewpoint of ease of handling and ease of product packaging, the designated mixing ratio (rate) is preferably within the range of 1 / 5 to 5 / 1 (mixing ratio: 20% to 500%) on a mass basis (or volume basis) (first agent / second agent), and more preferably within the range of 1 / 3 to 3 / 1 (mixing ratio: 33% to 300%).

[0074] The specified mixing ratio (rate) can be displayed on a mixing ratio (rate) information display medium. Examples of the mixing ratio (rate) information display medium include i) a product package made of a paper box or the like, ii) a product instruction manual provided as paper media and / or electronic data, iii) a container (bottle, syringe, packaging bag, etc.) in which the first and second agents are stored in a sealed state, iv) a product catalog provided as paper media and / or electronic data, and v) a communication sent to the product user by e-mail, mail, etc. separately from the product. The specified mixing ratio may also be provided to the product user in a manner that the product user can recognize in a manner other than those shown in i) to v) above.

[0075] When the kit of the present invention is used, the mixed composition (adhesive composition of the present invention) obtained by mixing the first partial composition (first agent) and the second partial composition (second agent) contains all kinds of chemical polymerization initiator components and polymerizable monomer components, and therefore polymerizes and hardens quickly or with a preset operation margin time. This allows a hardened body to be obtained. A known method can be used to polymerize and harden the mixed composition. For example, the mixed composition may be applied to a location where hardening is required and allowed to stand. In this case, the applied mixed composition can be kept at a temperature range of 10 to 37°C to allow the mixed composition to harden sufficiently. EXAMPLES

[0076] The present invention will be described below with reference to examples, but the present invention is not limited to the following examples.

[0077] 1. Abbreviations of substances used First, the abbreviations of the substances used in the chemical polymerization initiators and compositions containing the same in each of the Examples and Comparative Examples will be described below.

[0078] <(a) Thiourea compounds> AcTU; Acetylthiourea BzTU; Benzoylthiourea PTU; pyridylthiourea.

[0079] <(b) Peroxyester> BPT; t-Butylperoxy-3,5,5-trimethylhexanoate BPB; t-Butyl peroxybenzoate BPE; t-Butylperoxy-2-ethylhexyl monocarbonate BPL; t-butyl peroxylaurate.

[0080] <(c) Divalent copper compounds> CuA; copper(II) acetate monohydrate CuAA; Copper(II) acetylacetonate

[0081] <(d) Aryl borate compounds> PhBNa; sodium salt of tetraphenylboron PhBTEOA; triethanolammonium salt of tetraphenylboron.

[0082] <(e) Sulfite> SS; sodium sulfite.

[0083] <(f) Inorganic peroxide> NPS; Sodium peroxodisulfate KPS; potassium peroxodisulfate.

[0084] <(g) Acidic Group-Containing Polymerizable Monomer (Acidic Monomer)> MDP; 10-methacryloxydecyl dihydrogen phosphate SPM: A mixture of 2-methacryloyloxyethyl dihydrogen phosphate and bis(2-methacryloyloxyethyl)hydrogen phosphate in a molar ratio of 1:1.

[0085] <(h) Polymerizable monomers not containing an acidic group (non-acidic monomers)> BisGMA; 2,2-bis[4-(3-methacryloyloxy)-2-hydroxypropoxyphenyl]propane D-2.6E; 2,2-bis(methacryloyloxypolyethoxyphenyl)propane 3G; Triethylene glycol dimethacrylate HEMA; 2-Hydroxyethyl methacrylate UDMA; 2,2,4-trimethylhexamethylenebis(2-carbamoyloxyethyl) dimethacrylate.

[0086] <(i) Filler> F1: Silica zirconia filler with an average particle size of 3 μm F2: Silica zirconia filler with an average particle size of 0.2 μm.

[0087] 2. Examples 1 to 25 and Comparative Examples 1 and 2 The first agent (first partial composition) and the second agent (second partial composition) were prepared and mixed at a mass ratio of 1:1 to prepare adhesive compositions of each Example and Comparative Example, and evaluation was performed. Note that these adhesive compositions contain a filler, and the adhesive compositions of Examples 1 to 25 can be suitably used as dental cements. The preparation methods of the first and second agents, the evaluation methods, and the evaluation results are described below.

[0088] 2-1. Preparation method of the first and second agents First, as the polymerizable monomer component for the first agent used in Examples 1 to 8, Examples 10 to 25, and Comparative Examples 1 and 2, 50 parts by mass of a polymerizable monomer component for the first agent consisting of (h)BisGMA: 30 parts by mass and (h)3G: 20 parts by mass were prepared, and as the polymerizable monomer component for the first agent used in Example 9, 50 parts by mass of a polymerizable monomer component for the first agent consisting of (h)UDMA: 30 parts by mass and (h)3G: 20 parts by mass were prepared. Then, these polymerizable monomer components for the first agent: 50 parts by mass, (i) 116.5 parts by mass of a filler consisting of F1: 46.5 parts by mass and F2: 70 parts by mass, and a first partial initiator composition having the composition shown in Table 1 were mixed to prepare a first agent.

[0089] In addition, as the polymerizable monomer component for the second agent used in Examples 1 to 8, Examples 10 to 25, and Comparative Examples 1 and 2, 50 parts by mass of a polymerizable monomer component for the second agent consisting of 12.5 parts by mass of (g) MDP, 5 parts by mass of (h) HEMA, 20 parts by mass of (h) D-2.6E, and 12.5 parts by mass of (h) 3G were prepared, and as the polymerizable monomer component for the second agent used in Example 9, 50 parts by mass of a polymerizable monomer component for the second agent consisting of 12.5 parts by mass of (g) SPM, 5 parts by mass of (h) HEMA, 20 parts by mass of (h) D-2.6E, and 12.5 parts by mass of (h) 3G were prepared. Then, 50 parts by mass of these polymerizable monomer components for the second agent, (i) 116.5 parts by mass of a filler consisting of 46.5 parts by mass of F1 and 70 parts by mass of F2, and a second partial initiator composition having the composition shown in Table 1 were mixed to prepare the second agent.

[0090] In addition, the parts by mass (numbers in parentheses) of each component shown in Table 1 represent parts by mass relative to 50 parts by mass of the polymerizable monomer component for the first agent for the first partial initiator composition, and represent parts by mass relative to 50 parts by mass of the polymerizable monomer component for the second agent for the second partial initiator composition. That is, the components other than the polymerization initiator component of the first agent and the second agent in each example and comparative example are common, and the composition of the first agent and the second agent in each example and comparative example has a composition in which the first partial initiator composition and the second partial initiator composition having the composition shown in Table 1 are blended with the first agent base composition and the second agent base composition having the following composition, respectively. For example, the contents of (a), (e) and (d) in the first agent of Example 1 are, as shown in Table 1, BzTU: 0.5 parts by mass, SA: 3.3 parts by mass and PhBNa: 1.5 parts by mass, respectively.

[0091] (1) First agent base composition ·(h)BisGMA: 30 parts by mass ·(h)3G: 20 parts by mass ·(i)F1: 46.5 parts by mass ·(i)F2: 70 parts by mass (2) Base composition for second agent ·(g)MDP: 12.5 parts by mass ·(h)HEMA: 5 parts by mass ·(h)D-2.6E: 20 parts by mass ·(h)3G: 12.5 parts by mass ·(i)F1: 46.5 parts by mass ·(i)F2: 70 parts by mass

[0092] [Table 1]

[0093] 2-2. Various evaluation methods The first and second agents prepared as described above were mixed in a mass ratio of 1:1 to obtain adhesive compositions, and the bending strength of the cured bodies and the adhesive strength to dentin were evaluated. Furthermore, the adhesive strength to cobalt-chromium alloy was also evaluated for Examples 1 and 16 and Comparative Examples 1 and 2. The details of the measurement methods for bending strength, adhesive strength to dentin, and adhesive strength to cobalt-chromium alloy are shown below.

[0094] In each evaluation, in order to examine the storage stability of the first and second agents, two types of adhesive compositions shown in (a) and (b) below were used. (a) "As-prepared" adhesive composition An adhesive composition comprising a combination of a first part and a second part within 3 hours after preparation. (b) Adhesive composition "after storage" The adhesive composition after storing the first and second parts of the adhesive composition immediately after preparation shown in (a) above in separate containers at 50°C for 2 weeks.

[0095] 2-2-1. Bending strength measurement The adhesive composition prepared by the above method was filled into a polyacetal mold having a rectangular hole of 25 mm in length, 2 mm in width, and 2 mm in thickness, and left in a thermostatic chamber under humid conditions at 37°C for 60 minutes to cure. The obtained cured product was immersed in water at 37°C for 24 hours, and then burrs were removed using waterproof abrasive paper to obtain a measurement sample. Next, using a universal testing machine (AG-I type, manufactured by Shimadzu Corporation), a load was started at a crosshead speed of 1 mm / mm, and a load was applied to the test sample until the measurement sample broke, and the bending strength was calculated from the maximum load using the following formula (1). The results are shown in Table 8. Equation (1) Bending strength (MPa) = 3 × maximum load (N) × distance between support centers / (2 × width of specimen (mm) × thickness of specimen (mm) × thickness of specimen (mm)). In addition, this test is performed in an environment substantially free of water and oxidizing components, and therefore evaluates initiator activity in the substantial absence of water and oxidizing components.

[0096] 2-2-2. Measurement of adhesive strength to dentin The extracted bovine mandibular anterior tooth was polished with #600 waterproof abrasive paper under water, and the dentin plane was scraped off so that it was parallel to the labial surface. After blowing compressed air onto the dentin plane to dry it, a double-sided tape with a circular hole of 3 mm in diameter was fixed to each of them, and the adhesive area was determined. Next, the adhesive composition prepared by the above method was applied to a cylindrical metal attachment with a diameter of 8 mm, and the applied surface of the adhesive composition was pressed against the dentin surface so that the circular hole of the double-sided tape and the surface of the metal attachment were concentric. After immersing the test sample in water at 37°C for 24 hours, a universal testing machine (AG-I type, manufactured by Shimadzu Corporation) was used to start loading under the condition of a crosshead speed of 1 mm / mm, and a load was applied to the test sample until the measurement sample broke, and the adhesive strength was calculated from the maximum load using the following formula (2). Formula (2) Adhesive strength (MPa) = Maximum load (N) / Adhesive area (mm 2 ).

[0097] In order to demonstrate high adhesive strength to dentin, it is necessary for the portion of the adhesive composition that is in contact with the dentin, which contains a large amount of water and oxidizing components, and the portion that is distant from the dentin and contains almost no water or oxidizing components (the portion close to the metal attachment during testing) to polymerize sufficiently. Therefore, this test is an evaluation of whether polymerization activity is sufficient both in a system containing a large amount of water and oxidizing components and in a system containing almost no water and oxidizing components.

[0098] 2-2-3. Measurement of adhesive strength to cobalt-chromium alloy In order to more directly confirm the effect of water and oxidizing components on adhesive strength, test samples were prepared as follows for adhesive strength to cobalt-chromium alloy for (1) a system in which water and oxidizing components (hypochlorous acid) were not present, (2) a system in which water was present but an oxidizing component (hypochlorous acid) was not present, and (3) a system in which water and an oxidizing component were present. (1) Water and oxidizing component-free system: A cobalt-chromium alloy plate was polished with #800 and #1500 waterproof abrasive paper under water, and then subjected to high pressure sandblasting (4-5 kgf / cm from a distance of 0.5-1 cm).2 ), and then ultrasonically cleaned twice with ion-exchanged water and once with acetone. Next, the surface of the cleaned plate was dried by blowing compressed air onto it, and then a double-sided tape with a circular hole of 3 mm in diameter was fixed. Here, the area inside the circular hole of 3 mm in diameter was the adhesion area. Next, a mixed composition obtained by mixing the first agent and the second agent constituting the adhesive composition immediately after preparation or after storage was applied to the end surface of a cylindrical metal attachment of 8 mm in diameter. Then, the circular hole of the double-sided tape and the end surface of the metal attachment to which the mixed composition was applied were pressed together so that the central axes of both were aligned, to obtain a test sample. (2) Water present, oxidizing component absent: A test sample was prepared in the same manner as above, except that a double-sided tape with a circular hole of 3 mm in diameter was fixed in place and then water was applied to the inside of the hole using a cotton ball. (3) Water and oxidizing component present system: A test sample was prepared in the same manner as above, except that a double-sided tape with a circular hole of 3 mm in diameter was fixed in place and then hypochlorous acid water was applied to the inside of the hole using a cotton ball.

[0099] Next, these test samples were immersed in water at 37°C for 24 hours, and then a tensile load was applied to them at a crosshead speed of 1 mm / mm using a universal testing machine (AG-I type, manufactured by Shimadzu Corporation). At this time, the tensile load applied to the test sample was gradually increased until the adhesive surface of the test sample broke, and the adhesive strength was calculated from the maximum load at which breakage occurred using the above-mentioned formula (1). In this test, when hypochlorous acid water is applied inside the circular hole, it is evaluated whether the polymerization activity is sufficient in both systems where water and oxidizing components are present in large amounts and systems where they are almost absent. When water is applied inside the circular hole, it is evaluated whether the polymerization activity is sufficient in both systems where water is present in large amounts and systems where they are almost absent. When water is not applied inside the circular hole, it is evaluated whether the polymerization activity is sufficient in a system where there is almost no water.

[0100] 2-3.Evaluation results The evaluation results are shown in Tables 2 and 3.

[0101] [Table 2]

[0102] [Table 3]

[0103] As shown in Table 2, the adhesive compositions of Examples 1 to 25 showed good results in both bending strength and adhesive strength to dentin both immediately after preparation and after storage. These results demonstrated that the adhesive compositions of Examples 2 to 25 also had excellent curing properties, adhesive strength, and storage stability. In particular, the adhesive compositions of Examples 16 to 23, which contained an inorganic peroxide, showed even higher adhesive strength due to the synergistic effect with the sulfite.

[0104] The adhesive compositions of Examples 24 and 25 are examples in which only the combinations of the main components (a) to (e) constituting the first and second agents are changed from the adhesive composition of Example 1, and do not correspond to the kit of the present invention. Therefore, although the bending strength and adhesive strength of Examples 24 and 25 immediately after preparation are high like those of Example 1, the bending strength and adhesive strength after storage are lower than those of Example 1.

[0105] In Comparative Examples 1 and 2, the lack of sulfite resulted in high bending strength, but low adhesive strength to dentin. In Comparative Example 2, the inclusion of inorganic peroxide resulted in higher adhesive strength than Comparative Example 1, but lower than the example containing sulfite.

[0106] Moreover, as shown in Table 3, in Examples 1 and 16, high adhesive strength was shown regardless of the presence or absence of application of water or hypochlorous acid water. From these results, it was found that the adhesive compositions of these Examples have excellent curing properties and storage stability, and furthermore, show high adhesive strength regardless of the presence of water or oxidizing components. In particular, the adhesive composition of Example 16 showed higher adhesive strength when water was applied than when water was not applied. This result is considered to be the result of the sulfite and inorganic peroxide working effectively in the area where water is present, resulting in a synergistic effect.

[0107] On the other hand, the adhesive composition of Comparative Example 1 does not contain sulfite, so it is affected by the presence or absence of application of water or hypochlorous acid water, and when water or hypochlorous acid water is applied, the adhesive strength is greatly reduced. The adhesive composition of Comparative Example 2 does not contain sulfite but contains inorganic peroxide, so it shows high adhesive strength regardless of the presence or absence of application of water, but shows low adhesive strength when hypochlorous acid water is applied.

Claims

1. (a) a compound represented by the following general formula (1): 【Chemistry 1】 (In the formula, R 1 , R 2 and R 3 each represent a hydrogen atom, a substituted or unsubstituted alkyl group, a substituted or unsubstituted cycloalkyl group, a substituted or unsubstituted aryl group, a substituted or unsubstituted heterocyclic group, a substituted or unsubstituted acyl group, a substituted or unsubstituted aralkyl group, or a substituted or unsubstituted alkenyl group, and R 2 may be bonded to any group selected from R 1 and R 3 to form a ring.) A thiourea compound represented by the formula: (b) peroxy esters, (c) a divalent copper compound, (d) aryl borate compounds, and (e) contains a sulfite; A chemical polymerization initiator that is substantially free of hydroperoxide.

2. The chemical polymerization initiator according to claim 1, further comprising (f) an inorganic peroxide.

3. 3. The chemical polymerization initiator according to claim 1, wherein the sulfite (e) is sodium sulfite.

4. 4. An adhesive composition comprising: a radical-polymerizable monomer component consisting of (g) an acidic group-containing polymerizable monomer and (h) an acidic group-free polymerizable monomer; and the chemical polymerization initiator according to any one of claims 1 to 3, wherein the adhesive composition is substantially free of hydroperoxide.

5. 5. The adhesive composition of claim 4 further comprising: (i) a filler.

6. 6. The adhesive composition according to claim 4, which is a dental adhesive composition.

7. A kit for preparing the adhesive composition according to any one of claims 4 to 6, comprising: The present invention comprises a combination of a first partial composition and a second partial composition packaged in such a way that they cannot come into physical contact with each other; the first partial composition contains the (a) thiourea compound, the (d) aryl borate compound, and the (e) sulfite, and is substantially free of the (c) divalent copper compound, the (g) acidic group-containing polymerizable monomer, and the (e) peroxide; the second partial composition contains the (b) peroxy ester, the (c) divalent copper compound, and the (g) acidic group-containing polymerizable monomer, and is substantially free of the (a) thiourea compound, the (d) aryl borate compound, and the (e) sulfite; At least one composition selected from the first partial composition and the second partial composition further contains the (h) acidic group-free polymerizable monomer. A kit for preparing an adhesive composition comprising:

8. 8. The adhesive composition preparation kit according to claim 7, wherein at least one of the first partial composition and the second partial composition further comprises (i) a filler.

Citation Information

Patent Citations

  • Chemical polymerization catalyst for dental use

    JP2002187907A

  • Dental curable composition

    JP2014152106A

  • Manufacturing method of adhesive polyaryletherketone resin material and adhering method

    JP2017088637A

  • Dental polymerizable composition

    JP2018002649A

  • Chemical polymerization initiator, adhesive composition, adhesive composition kit, dental material, dental material kit and storage method of adhesive composition

    JP2020111513A